2022
DOI: 10.3389/fcell.2022.876510
|View full text |Cite
|
Sign up to set email alerts
|

A2A Receptor Contributes to Tumor Progression in P2X7 Null Mice

Abstract: ATP and adenosine are key constituents of the tumor niche where they exert opposite and complementary roles. ATP can be released in response to cell damage or actively released by tumor cells and subsequently degraded into adenosine, which accumulates within the tumor microenvironment. Notably, while ATP promotes immune eradicating responses mainly via the P2X7 receptor (P2X7R), extracellular adenosine acts as a potent immune suppressor and facilitates neovascularization thanks to the A2A receptor (A2AR). To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…We demonstrate that using MVA-OVA-infected feeder cells bearing the active P2X7 receptor led to a significantly higher CD8 + T cell activation as determined by IFNү production in B8R- specific T cells or by TNFα production in either B8R- or OVA-specific T cell lines when co-cultured with uninfected dendritic cells as cross-presenting APC ( Figure 2A ). These data are in line with the P2RX7-dependent release of these cytokines in mice ( 45 ). The frequency of cross-presenting BMDCs with SIINFEKL/H2-K b complexes on the cell surface, as well as the amount of these peptide/MHCI complexes per cell, was significantly increased ( Figure 2B left, middle).…”
Section: Resultssupporting
confidence: 87%
“…We demonstrate that using MVA-OVA-infected feeder cells bearing the active P2X7 receptor led to a significantly higher CD8 + T cell activation as determined by IFNү production in B8R- specific T cells or by TNFα production in either B8R- or OVA-specific T cell lines when co-cultured with uninfected dendritic cells as cross-presenting APC ( Figure 2A ). These data are in line with the P2RX7-dependent release of these cytokines in mice ( 45 ). The frequency of cross-presenting BMDCs with SIINFEKL/H2-K b complexes on the cell surface, as well as the amount of these peptide/MHCI complexes per cell, was significantly increased ( Figure 2B left, middle).…”
Section: Resultssupporting
confidence: 87%
“…Hence, the impact of P2X7 on cancer growth versus tumor immune control is complicated. Indeed, we and others demonstrated that a lack of host P2X7, for example in null mice, could favor tumor growth by significantly reducing immune infiltrates and pro-inflammatory cytokines and increasing intratumoral Tregs and adenosinergic pathways related to immune suppression [ 15 , 80 , 81 , 82 , 83 , 84 ]. However, even in P2X7 null-hosts, when an implanted tumor expresses P2X7, the administration of P2X7 antagonists causes a significant reduction in neoplastic growth accompanied by a substantial increase in CD4 + infiltrates, and also a decrease in the expression of the fitness marker CD73 in Tregs [ 15 ].…”
Section: The P2x7 Receptor In Cancer Growth and Immune Responsesmentioning
confidence: 99%
“…Correspondingly, the deficiency of host P2X7R leads to the decrease of CD8 and Teff cells and the increase of immunosuppressive Tregs, contributing to cancer progression 143 . In the absence of host P2X7R, the increased expression of A2AR receptors promotes tumor growth by inducing immune suppression and neovascularization 190 . Moreover, under the transient stimulation of low concentration of eATP and its analogs, P2X7R opens the channel allowing small cations to permeate, promoting tumor cell proliferation and immune response.…”
Section: Immunotherapy Against P2x7rmentioning
confidence: 99%